Gemcitabine and glioblastoma: challenges and current perspectives. Issue 2 (February 2018) - Bastiancich, Chiara; Bastiat, Guillaume; Lagarce, Frederic
Highlights: New drugs are required to treat glioblastoma and limit resistance. Gemcitabine displays specific advantages over temozolomide. Gemcitabine immunomodulating capacity could be useful to cure glioblastoma. Gemcitabine administered concurrently with radiotherapy is safe in humans. Alternative drug delivery strategies are proposed to enhance gemcitabine efficiency. Abstract : Gemcitabine is a nucleoside analog currently used for the treatment of various solid tumors as a single agent or in combination with other chemotherapeutic drugs. Its use against highly aggressive brain tumors (glioblastoma) has been evaluated in preclinical and clinical trials leading to controversial results. Gemcitabine can inhibit DNA chain elongation, is a potent radiosensitizer and it can enhance antitumor immune activity, but it also presents some drawbacks (e.g., short half-life, side effects, chemoresistance). The aim of this review is to discuss the challenges related to the use of gemcitabine for glioblastoma and to report recent studies that suggest overcoming these obstacles opening new perspectives for its use in the field (e.g., gemcitabine derivatives and/or nanomedicines).